The Problem of Career Orientation and Reorientation - Jatautaitė, Birutė (Acta Paedagogica Vilnensia, 1991)
The article focuses on the problems of career orientation and reorientation. While noting that career guidance practiced in schools for a long time has been often confined to agitation, it is proposed to view the career guidance as a complex problem. It should benefit not only from the theories of pedagogy, but also psychology and sociology. The article gives a brief overview of the variety of these theories, distinguishing insights of individual scientists on the connection of the choice of profession with early childhood experiences, directedness of mental energy and needs (A. Roe), personality traits and environmental role (J.L. Holland, D.E. Super), the activities and plans for the future (E. Cinzberg). One of the parts of this integrated approach to career orientation certainly is the problem of professional re-orientation (conversion). Its occurrence depends on many difficulties experienced by students, related to the unrealistic choice, indeterminacy of fundamental values, skills, lack of steady motives, self-esteem, problems of adaptation, professional fitness.